Intelligent Technologies for Interactive Entertainment : 10th EAI International Conference, INTETAIN 2018, Guimarães, Portugal, November 21-23, 2018, Proceedings /: 10th EAI International Conference, INTETAIN 2018, Guimarães, Portugal, November 21-23, 2018, Proceedings. (2019) - Unknown
No abstract available